Diffused-Line-of-Sight Communication for Mobile and Fixed Underwater Nodes - Yujian Guo; Meiwei Kong; Omar Alkhazragi; Xiaobin Sun; Mohammed Sait; Tien Khee Ng; Boon S. Ooi (IEEE Photonics Journal)
The misalignment of mobile underwater wireless optical communication (UWOC) systems, compounded by turbulence in underwater scenarios, is a practical problem that can be resolved through various means. This work describes a pulse-position-modulation-based (PPM-based) diffused-line-of-sight UWOC system that offers a solution to this issue. PPM is found to be power-efficient and, in terms of bit-error-ratio performance, outperforms on-off keying modulation and orthogonal frequency-division multiplexing modulation in complex dynamic underwater channels. Through indoor experiments and outdoor deployment, we validated the robustness of the proposed PPM-based mobile UWOC system. This work sheds light on the practical implementation of UWOC networks for relieving the strict pointing-acquisition-and-tracking requirements when an underwater apparatus is transmitting or receiving signals on the fly.